53. FACTORS FACTORS ASSOCIATED WITH ANXIETY DISORDERS AMONG CARDIOVASCULAR PATIENTS IN SOC SON DISTRICT, HANOI IN 2023 (Vietnam Journal of Community Medicine, 2026)
Objective: This study was conducted to identify factors associated with anxiety disorders among cardiovascular patients in Soc Son District, Hanoi in 2023. Methods: A cross-sectional descriptive study was conducted on 418 cardiovascular patients who visited seven communes health stations in Soc Son District from June to July 2023. Data was collected using the DASS21 scale. Results: Educational level and duration of illness were found to be associated with anxiety disorders among cardiovascular patients. Patients with intermediate or college education were 3.02 timesmore likely to experience anxiety compared to those with a high school education or below. Additionally, those who had been ill for 16–20 years were 6.39 times more likely to suffer from anxiety than those with a duration of illness of 11–15 years. Conclusion: Early screening and intervention targeting risk factors such as educational level and duration of illness may help reduce the negative impact of anxiety on cardiovascular treatment outcomes.